Practicality of Augmented Reality Books in Physics Learning: A Literature Review - Arzak, Kirana Aureola; Prahani, Binar Kurnia (JPPS (Jurnal Penelitian Pendidikan Sains), 2023)
In the digital era, the rapid development of science and technology provides convenience in teaching and learning; media is needed to provide practicality in supporting learning. Augmented Reality media is a practical solution as a learning medium in visualizing a material when the learning process, especially in physics, requires more visualization for the concepts displayed.  Objective: This research analyzes the practicality of augmented reality learning media in physics learning.  Methods: Descriptive research using the literature review method to find out, identify, assess, and interpret related to the augmented reality book practicality research obtained from various sources such as journals, books, and the internet. The literature review method analyzes, identifies, and provides interpretation and evaluation of some existing research that is relevant to the research topic.  Results: Through studies conducted using the literature review method, it can be found that: 1) Augmented reality in education has yet to be widely implemented and applied as a supporting medium for interactive education in schools. 2) The application of augmented reality is a practical solution for educators to support them in providing knowledge to students in addition to video conferencing. 3) The practicality of augmented reality books in physics learning is valid. 4) The use of augmented reality books in physics learning is considered to improve the quality of student learning.  Novelty:  Previous researchers have never done this research, which analyzes the practicality of augmented reality learning media in physics learning.